Education: a chance to change organ shortage. Should we address a different message to society? - Cantarovich, Félix (Medicina e Morale, 2002)
This paper attempts to provide burdens insights into the problem of shortage of donor organs for transplantation and offers a prescription of a new approach to obtaining organs from individuals who have just died. The fundamental theses advanced here are that there is a need for education of the public, and especially the youth among the people, to the fact that their commitment to consent to use organ for transplantation represents an insurance policy for their own future health and that organ transplantation is a needed part of expensive medical care, not unlike other modalities of treatment. Central to this educational strategy are two concepts: 1. erase the concept of the integrity of the cadaver, focusing instead on the usefulness of the organs of the cadaver to solve a societal need; 2. to establish, as a principle, that the use of cadaver organs means to share a source of health for humankind.